KEPEMIMPINAN GURU DALAM PELAKSANAAN TUGASNYA DI KELAS - Ermita Ermita (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
This paper to aim at desription about teacher’s leadership in accomplishment their task in class which analyse from education function and instructional function. Teacher’s leadership in educate can be performed by ways (a) give motivation to studens; teachers have to motivate studens in their’s behavior change process to better and better behavior. (b) To Guide studens; Teachers have to guide studens which behave are’t reconcile with norms. (c) To direction ; Teachers must be controll and direct studen’s activities, so that studens will not behave that to collide with norms. Teacher’s leadership in intructional can be performed by (a) give motivation to studens; teachers have to motivate studens in instructional process by technics select and use variation instructinal methods. (b) To Guide studens; Teacher must to guide student increase their achievement by technics direct training and assistance in exercises , (c) To direction; Teachers must be can to direct students in instructional process clearly, so that easy to be understood.